(untitled) (Research, Society and Development, 2019)
The aim of this article is to present the results of experienced reading practice in a basic education school in the city of Santa Maria / RS. This study aims to share an experience report in a Municipal School of Elementary Education located in the city of Santa Maria, RS, Brazil, regarding the reading practices in the classroom through the project "Vanguarda Escolar". This experience consists of the approach of facts, news, documentaries, selected by the students of a fifth grade class of elementary school I. The project occurs weekly, with the presentation of themes, randomly, listed by the students mediated by the class teacher. To support the discussion theoretically, authors such as Soares, Rojo, Kleimann, among others were used. The results show that the reading practices developed in the school context made possible a more meaningful learning for the students participating in the project, contributing to a more critical-reflexive formation